Manajemen Stress Psikologis untuk Pengendalian Tekanan Darah dengan Hipnoterapi Pada Kelompok Penderita Hipertensi RW I Mersi Kabupaten Banyumas - Setyo, Arif; Isworo, Atyanti; Ekowati, Wahyu (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2022)
The impact of the COVID-19 pandemic causes both physical and psychological stress, especially for people with hypertension. Stress conditions in patients with hypertension can cause uncontrolled blood pressure. The results of the interview with the Chair of the Sehati hypertension group revealed that the problem faced by sufferers during this pandemic was uncontrolled blood pressure as a result of psychological stress. The solutions offered include non-pharmacological psychological stress management training, training in measuring blood pressure and stress levels, as well as hypnotherapy training for controlling blood pressure and psychological stress in patients with hypertension. The results obtained included 100% of participants being able to mention non-pharmacological methods to control psychological stress, 93.33% of participants being able to explain the measurement of psychological stress, 86.67% able to demonstrate the use of hypnotherapy for stress control, 100% of participants who demonstrated a decrease in stress levels. psychologically from a score of 4-6 (moderate stress) to a score of 1-3 (mild stress) and showed a decrease in blood pressure. The implementation of training is effective in increasing the knowledge and skills of hypertension sufferers in managing psychological stress.